Perceptions about the labor insertion of people with disabilities (ADA) in Mar del Plata (AACINI - International Journal of Industrial Engineering, 2024)
The insertion of Persons with Disabilities (ADA) is an issue that requires treatment, study and understanding given that although there are regulations aimed at increasing the access of this group to the labor market, reality shows that it is far from being able to increase equal opportunities. This article presents partial results of an exploratory study that is part of a larger research project, entitled: "Integration of people with disabilities (ADA): mechanisms for selection, incorporation, evaluation and development of skills in organizations", which is frameworked in an inter-institutional link between UNLu and UNMDP. For this qualitative survey, semi-structured interviews are taken to key actors, forming an intentional non-probabilistic sample (N=7), belonging to five organizations in order to determine which are the variables that make up the dimensions of analysis to be considered as determinants for the understanding of ADA insertion. The data treatment is carried out through a discursive analysis, in a triple helix: informational, social-hermeneutic and antinomic pairs. With this contribution is expected to provide data that account for the labor insertion of the group studied and the determined organizational context, to contribute to the understanding and awareness of said subject.
Keywords: management; persons with disabilities; labor insertion; engineering